Archeology and Genealogy, Conceptual Operators For The Research In Educa - Sosa Gutiérrez, Pedro Alexander; Chaparro Cardozo, Elver (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The article approach is revolved around uses and forms of appropriation of some Foucault’s archeology and genealogy categories and concepts as conceptual operators that permit new approaches in the education field. To this end, such categories are revised for the research in education. Thus, the text describes the possibilities and the limitations of these categories; like a toolbox to face the task of researching in education and pedagogy.